Brazilian Political Institutions: an Inconclusive Debate - Palermo, Vicente Antonio (2016)
The debate about the operation of Brazilian political institutions is far from conclusive. It could hardly be different, since current Brazilian democratic regime is only 30 years-old. This article updates a previous one, published in 2000, in which I discuss different and rival interpretations on the functioning of the Brazilian democracy. Some new works argue that a 'dialectic synthesis' of those strands has been recently produced. This article demonstrates this argument is not accurate. Instead, my main argument is that, in spite of rich analyses, new evidences and some displacements, the interpretations and paradigms guiding that debate remain the same. On the other hand, in spite of the solid position of the interpretation sustaining how the Brazilian political system ensures governability, the current institutional debate goes far beyond this paradigm by setting new themes and approaches. To demonstrate this argument, the article presents the evolution of such debate.